Ambidextrous Leadership: Mitigating Turnover Intentions in Millennial Workforce - Prasetyo, Johan Hendri; Triyadi, Triyadi; Karunia, R. Luki; Janiah, Samrotul; Mazia, Lia (Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: This study aims to decrease the intention of millennial employees to leave startup companies in Indonesia through the roles of Ambidextrous Leadership, Work-Life Balance, Career Development, and job satisfaction. Background Problems: The startup industry in Indonesia is rapidly growing alongside advancements in information and communication technology, yet still faces high turnover rates. Novelty: The uniqueness of this research lies in its focus on Ambidextrous Leadership, which combines exploration, exploitation, and flexibility, aligning well with the millennial generation's penchant for change and the development of new ideas in startup companies. Research Methods: This research adopts a quantitative method with a causal research design. A sample of 300 respondents is chosen through the snowball sampling technique. Data analysis involves utilizing SEM-PLS to examine the research hypotheses. Finding/Results: In the context of startup companies, Ambidextrous Leadership, Work-Life Balance, and Career Development play crucial roles in enhancing job satisfaction and reducing employee Turnover Intention. Conclusion: The managerial implication is that startup company leaders need to adopt an Ambidextrous Leadership approach, prioritize Work-Life Balance, and provide clear Career Development opportunities to retain talent and improve employee satisfaction.